Pathophysiology of IL-33 and IL-17 in allergic disorders. (December 2017) - Gupta, Rinkesh Kumar; Gupta, Kriti; Dwivedi, Premendra D.
Graphical abstract: Highlights: Recently, pathogenic role of IL-17 and IL-33 have been found in various allergic disorders. Mast cells and certain epithelial cells secrete IL-33 cytokine in response to external stimulus. IL-17 secreted by Th17 cell, acts upon various immune cells. Group 2 innate lymphoid cells (ILC2s) have been found to be associated with both cytokines. Abstract: Allergic diseases are among common clinical conditions, affecting millions of children and adults throughout the world. Food allergies, skin allergies (atopic dermatitis), and respiratory allergies (allergic rhinitis and asthma) are the common types of allergies. Recently discovered cytokines IL-17 and IL-33 have been found to play an important role in the pathogenicity of various hypersensitive disorders. After exposure to allergens or infection with parasites or viruses, IL-17 and IL-33 producing cells, such as Th17 and specialized epithelial cells respectively, become activated and trigger the pathogenic immune responses in different susceptible conditions. Potent inhibitors of these cytokines have been identified recently that may represent potential therapeutic agents to overcome the clinical complications of allergies. In the present review, we have discussed the cellular sources, modes of action and regulation of IL-17 and IL-33 in the context of hypersensitive diseases. We have also assessed the therapeutic potential of inhibitory molecules that may alter production of both these cytokines, and thus modulate susceptible conditions.